El horror en fragmentos: Eduardo Galeano y la memoria histórica de los derechos humanos latinoamericanos (Altre Modernità, 2019)
The work of Galeano, precursor of a whole work on the Latin American horrors has not been taken into account enough by the academy, for this critical deficit I wanted to take his work Memory of Fire, the work of a forceful goldsmith, because the author resorts to 227 books, letters and first generation colonial works to pose the Latin American colonial condition, usurpation, terror and militarism since the time of the Conquest.The work analyzes the importance of the past to know the present, there are often big gaps around phenomena of repression that already took place in other centuries and recognizing it to make new generations aware that seek social justice. This work is also supported by two discussions: the use of the literary fragment to present the due history and the "abysmal" thought of Boaventura de Sousa Santos, a decolonial critic par excellence. I use Boaventura de Sousa because to speak about Latin America we need to use the critics of our continent, who have a sharp look based on regional experiences of absences and death.